Case Report: Upper limb superficial venous thrombosis associated with oral contraceptives mimicking soft tissue mass - Song, Jun Hyeong; Chun, Kyoung-Chul; Han, Gwan Hee; Yang, Seung-Woo; Yoon, Sang-Hee; Yuk, Jin-Sung; Ahn, Jaeki; Nam, Sang Hyun; Kim, Jongwoo; Kim, Myounghwan (Frontiers in Cardiovascular Medicine, 2023)
Background Venous thrombosis associated with the use of oral contraceptives (OCs) occurs mostly in the deep veins of the lower extremity. A lesion of the upper extremity is rare, and the majority of thrombotic events that occur in the superficial vein of the upper extremity are caused by intravenous catheters. We present a rare case of superficial venous thrombus on the upper extremity in a woman with a history of long-term OC use. Case presentation A 35-year-old woman, with an 8-year history of OC use, presented with a 2-year history of painfully palpable masses on her left forearm. The lesion mimicking soft tissue mass was confirmed to be superficial venous thrombi through ultrasound and magnetic resonance imaging. Conservative treatment including non-steroidal anti-inflammatory drugs, vasoprotective agents, and aspirin was prescribed. Through consultation with the Department of Obstetrics and Gynecology, it was confirmed that the current OCs could be discontinued, and the pain was almost relieved after conservative treatment. Conclusions If thrombotic events occur in the superficial vein of the upper extremity without intravenous catheters, detailed medical history taking and the possibility of OCs should be considered.